Nilai manfaat ekonomi daerah aliran Sungai Oyo Kabupaten Gunungkidul - Benito, Obed Juan; Purwaningrat, Adib Wahyu; Azzahra, Naura Yanda; Shahniar, Surya Taufiq (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2023)
The existence of the Oyo Watershed provides many benefits to the people of Yogyakarta. The direct benefit of the Oyo Watershed is to meet the community's clean water needs. This benefit is considered to have economic value so that it can be measured in units of currency and needs to be assessed. The assessment of the watershed aims to determine the economic value of the Oyo Watershed which flows in Gunungkidul Regency, Yogyakarta. The economic value is calculated using a market data-based approach and the replacement cost method. There are three alternatives used in the calculation, namely the cost of replacing the value of water in the form of water from PDAM production of IDR 177,896,643,185/year, the cost of clean water from tankers of IDR 2,928,668.050.000/year, and the cost of clean water from drilled wells of IDR 376,291,597,500/year. Of the three alternatives, the most cost-effective alternative is taken to replace the existence of the Oyo Watershed, resulting in an economic value of IDR 177,896,643,000/year (rounded up).